Distribution and behaviour of dissolved selenium in tropical peatland-draining rivers and estuaries of Malaysia - Aazani, Mujahid; Mohd Fakharuddin, Muhamad; Sien, Edwin Aun Sia; Holt, Faddrine Ajon Jang; Yan, Chang; Müller, Moritz; Ying, Wu; Shan, Jiang; Wan, Wan Cao; Jian, Guo Qu; Jing, Ling Ren; Xiao, Na Wang (Copernicus Publications on behalf of the European Geosciences Union, 2020)
Selenium (Se) is an essential micronutrient for aquatic organisms. Despite its importance, our current knowledge of the biogeochemical cycling of dissolved Se in tropical estuaries is limited, especially in Southeast Asia. To gain insights into Se cycling in tropical peat-draining rivers and estuaries, samples were collected from the Rajang, Maludam, Sebuyau, Simunjan, Sematan, Samunsam and Lunda rivers and estuaries in western Sarawak, Malaysia, in March and September 2017 and analysed for various forms of Se (dissolved inorganic and organic). Mean total dissolved Se (TDSe), dissolved inorganic Se (DISe) and dissolved organic Se concentrations (DOSe) were 2.2 nmol L−1 (range: 0.7 to 5.7 nmol L−1 ), 0.18 nmol L−1 (range: less than the detection limit to 0.47 nmol L−1 ) and 2.0 nmol L−1 (range: 0.42 to 5.7 nmol L−1 ), respectively. In acidic, low-oxygen, organicrich blackwater (peatland-draining) rivers, the concentrations of DISe were extremely low (near or below the detection limit, i.e. 0.0063 nmol L−1 ), whereas those of DOSe were high. In rivers and estuaries that drained peatland, DOSe / TDSe ratios ranged from 0.67 to 0.99, showing that DOSe dominated. The positive relationship between DISe and salinity and the negative relationship between DOSe and salinity indicate marine and terrestrial origins of DISe and DOSe, respectively. The positive correlations of DOSe with the humification index and humic-like chromophoric dissolved organic matter components in freshwater river reaches suggest that peat soils are probably the main source of DOSe The DOSe fractions may be associated with high molecular weight peatland-derived aromatic and black carbon compounds and may photodegrade to more bioavailable forms once transported to coastal waters. The TDSe flux delivered by the peat-draining rivers exceeded those reported for other small rivers and is quantitatively more significant than previously thought.